Querying data in NoSQL databases - Babić, Andrea, informatičarka; Jakšić, Danijela; Poščić, Patrizia (2019)
The goal of this paper is to give an overview of fundamental concepts and types of NoSQL databases, to show some examples of database queries, some related research, and the implementation of those queries in an original practical example. The introduction is a brief representation and description of the NoSQL database. There are also several comparisons of NoSQL database with the relational database. The next chapter contains a review of the basic NoSQL databases and their prototypes. In each of the following subchapters, the types of NoSQL databases are described in more detail and various queries which can be performed over them are presented. In the last chapter there is also a practical example of querying one of these databases.
Zadatak rada bio je istražiti NoSQL baze podataka, fokusirati se na izvođenje upita nad njima, opisati neke od dosadašnjih istraživanja te prikazati izvršavanje tih upita na vlastitom praktičnom primjeru. U uvodu su ukratko predstavljene i opisane NoSQL baze podataka. Prikazano je i nekoliko usporedbi s relacijskom bazom podataka. U idućem poglavlju možemo vidjeti pregled osnovnih NoSQL baza podataka te njihove prototipe. U svakom od sljedećih potpoglavlja detaljnije su opisane vrste NoSQL baza podataka i prikazani razni upiti koji se mogu izvoditi nad njima, a u posljednje poglavlje uključen je i vlastiti praktični primjer izvođenja upita nad jednom od tih baza.
Bibliografija: 12 jed.
Summary ; Sažetak.
Keywords: NoSQL -- Baze podataka -- Relacijske baze podataka -- Dokumentne baze -- Upiti